ENSAM: Europium Nanoparticles for Signal enhancement of Antibody Microarrays on nanoporous silicon. - Järås, K; Tajudin, A; Ressine, A; Soukka, T; Marko-Varga, G; Bjartell, A; Malm, J; Laurell, T; Lilja, H (2008)
To improve the sensitivity of antibody microarray assays, we developed ENSAM (Europium Nanoparticles for Signal enhancement of Antibody Microarrays). ENSAM is based on two nanomaterials. The first is polystyrene nanoparticles incorporated with europium chelate (beta-diketone) and coated with streptavidin. The multiple fluorophores incorporated into each nanoparticle should increase signal obtained from a single binding event. The second nanomaterial is array surfaces of nanoporous silicon, which creates high capacity for antibody adsorption. Two antibody microarray assays were compared: ENSAM and use of streptavidin labeled with a nine-dentate europium chelate. Analyzing biotinylated prostate-specific antigen (PSA) spiked into human female serum, ENSAM yielded a 10-fold signal enhancement compared to the streptavidin-europium chelate. Similarly, we observed around 1 order of magnitude greater sensitivity for the ENSAM assay (limit of detection < or = 0.14 ng/mL, dynamic range > 10(5)) compared to the streptavidin-europium chelate assay (limit of detection < or = 0.7 ng/mL, dynamic range > 10(4)). Analysis of a titration series showed strong linearity of ENSAM ( R2 = 0.99 by linear regression). This work demonstrates the novel utility of nanoparticles with time-resolved fluorescence for signal enhancement of antibody microarrays, requiring as low as 100-200 zmol biotinylated PSA per microarray spot. In addition, proof of principle was shown for analyzing PSA in plasma obtained from patients undergoing clinical PSA-testing.